2020
DOI: 10.3390/antibiotics9100709
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Human Periodontal Pathogen Parvimonas micra Over 10 Years

Abstract: Changes were evaluated over 10 years in the in vitro resistance of human periodontopathic strains of Parvimonas micra to four antibiotics. Subgingival biofilms culture positive for P. micra from 300 United States adults with severe periodontitis in 2006, and from a similar group of 300 patients in 2016, were plated onto anaerobically incubated enriched Brucella blood agar alone, or supplemented with either doxycycline (4 mg/L), clindamycin (4 mg/L), amoxicillin (8 mg/L), or metronidazole (16 mg/L). P. micra gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
1
19
0
4
Order By: Relevance
“…To our knowledge, there is one report that evaluated the antibiotic resistance of periodontal pathogens over time. This report showed that Parvimonas micra resistance to AMPC remained low in 2016 compared with 2006 (2.3% vs. 1.0% of patients) 15 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, there is one report that evaluated the antibiotic resistance of periodontal pathogens over time. This report showed that Parvimonas micra resistance to AMPC remained low in 2016 compared with 2006 (2.3% vs. 1.0% of patients) 15 …”
Section: Discussionmentioning
confidence: 80%
“…This report showed that Parvimonas micra resistance to AMPC remained low in 2016 compared with 2006 (2.3% vs. 1.0% of patients). 15 Thus, it is difficult to posit that antimicrobial resistance was the cause. Second, the difference in prophylactic antibiotics alone may not be sufficient to control clinical outcomes in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these underlying conditions can cause severe disruption of and a reduction in the strength of a patient's autoimmune system, which likely led to infection of this patient's lower back with P. micra at first. For the treatment of P. micra infection, penicillin, metronidazole, and clindamycin are usually preferred ( 8 ). Our patient was initially treated with a 3-day infusion of piperacillin–tazobactam, but her infection was not controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of antibiotic resistance increased within the last decades and is one of the biggest challenges in medicine, particularly in dentistry [81][82][83]. The development of alternative strategies for antimicrobial defense is one of the challenges of contemporary dental research [84].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%